Wild chocolate : across the Americas in search of cacao's soul - Jacobsen, Rowan (Bloomsbury Publishing, 2024)
"From James Beard Award-winner Rowan Jacobsen, the thrilling story of the farmers, activists, and chocolate makers fighting all odds to revive ancient cacao and produce the world's finest bar." --